The epidemiology of cryptococcosis and the characterization of Cryptococcus neoformans isolated in a Brazilian University Hospital - Paula Augusta Dias Fogaça de Aguiar; Reginaldo dos Santos Pedroso; Aércio Sebastião Borges; Tomaz de Aquino Moreira; Lúcio Borges de Araújo; Denise Von Dolinger de Brito Röder (Revista do Instituto de Medicina Tropical de São Paulo)
ABSTRACT Cryptococcosis, a systemic disease caused by the fungus Cryptococcus neoformans/ Cryptococcus gattii is more severe in immunocompromised individuals. This study aimed to analyze the epidemiology of the disease, the molecular characteristics and the antifungal susceptibility of C. neoformans isolated from patients treated in a Brazilian university hospital. This retrospective study was conducted in the Clinical Hospital, Federal University of Uberlândia, and evaluated cases of cryptococcosis and strains of C. neoformans isolated from 2004 to 2013. We evaluated 41 patients, 85% of whom were diagnosed with AIDS. The fungus was isolated from the cerebrospinal fluid (CSF) of 21 patients (51%); 19.5% had fungemia and in 24% the agent was isolated from the CSF and blood, concurrently. Meningoencephalitis was the most frequent (75%) manifestation of infection. Despite adequate treatment, the mortality of the disease was 58.5%. Most isolates (97.5%) presented the VNI genotype (serotype A, var. grubii) and one isolate was genotyped as C. gattii (VGI); all the isolates were determined as mating type MATa and showed susceptibility to the tested antifungals (fluconazole, voriconazole, amphotericin B and 5-flucytosine). Although AIDS detection rates remain stable, opportunistic infections such as cryptococcosis remain as major causes of morbidity and mortality in these patients.